Analisis Tipologi dan Pengembangan Kawasan Pesisir Kota Bontang (Studi Kasus Kelurahan Tanjung Laut Indah, Kelurahan Bontang Kuala dan Kelurahan Guntung) - Bia Musa; Muhammad Lukman Hakim (Program Studi Ilmu Pemerintahan Universitas Islam Raden Rahmat Malang, 2020)
Abstract The city bontang is a city in east kalimantan commonly used as a groove, shipping good grooves, private shipping the people and national shipping. groovesThis study attempts to analyze the condition of urban village bontang, kelurahan-kelurahan coastal cities researchers to 3 villages namely, bontang, kuala urban village tanjung sea beautiful and guntung. urban villageIn preparing tipologi-tipologi coastal villages are based on aspects of economic and buday, sosisl and draw up strategic langkah-langkah. area developmentMethods used in this research is a qualitative methodology.Data collection techniques in research is observation and interview.The research results show that typologies and development urban village urban village coastal city bontang on 2016 and 2017 of each of the kelurahan was as follows: urban village bontang kuala decreased as much as two points , and judgment the field of regional and sociological urban village bontang kuala has not changed any .Urban village guntung decreased by one points , assessment the field of regional guntung urban village has not changed any and judgment the field of kemasayarakatan urban village guntung decreased as much as two points .Tanjung the sea beautiful on 2016 to 2017 increased as many as 13 points . While a strategy that was done to the development of urban village in the region coastal cities bontang covering 4 stretagi, among them are: 1 ) optimization of fisheries production through the cultivation of fisheries products, ; 2 ) the optimization of the role of fish market and personnel to the marketing of the sea; 3 ) strengthening community facilities and infrastructure to fishermen; and 4 ) strengthening efforts to conservation and rehabilitation. coastal ecologicalAll four of the strategy has been done by masing-masing, village namely bontang, kuala guntung and tanjung sea beautiful with very good.